2020
DOI: 10.1175/jtech-d-19-0159.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Synthetic Arctic Argo-Type Floats in a Coupled Ocean–Sea Ice State Estimation Framework

Abstract: The lack of continuous spatial and temporal sampling of hydrographic measurements in large parts of the Arctic Ocean remains a major obstacle for quantifying mean state and variability of the Arctic Ocean circulation. This shortcoming motivates an assessment of the utility of Argo-type floats, the challenges of deploying such floats due to the presence of sea ice, and the implications of extended times of no surfacing on hydrographic inferences. Within the framework of an Arctic coupled ocean–sea ice state est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…The model‐data misfit y ( t )− E ( t ) x ( t ) is weighted by the inverse error covariance matrix R ( t ). This accounts for both observational uncertainty and model representation error, where the latter considers the extent to which real variability cannot be represented at the chosen model resolution (Nguyen, Heimbach et al., 2020). B ( t 0 ) and Q ( t ) are error covariances of x 0 and u ( t ), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model‐data misfit y ( t )− E ( t ) x ( t ) is weighted by the inverse error covariance matrix R ( t ). This accounts for both observational uncertainty and model representation error, where the latter considers the extent to which real variability cannot be represented at the chosen model resolution (Nguyen, Heimbach et al., 2020). B ( t 0 ) and Q ( t ) are error covariances of x 0 and u ( t ), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As is common in data assimilation (Janjić et al., 2017) the ECCO framework utilizes “representation errors”—described above—in the weighting of the model‐data misfits, Equation , to safeguard against over‐fitting and facilitate more meaningful model‐data comparison (Wunsch & Heimbach, 2007). However, these representation errors are themselves highly uncertain, often relying on unconstrained high‐resolution model runs from which they are inferred (see Nguyen, Heimbach et al., 2020, for a more detailed discussion).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, their use under sea ice will require appropriate deployment strategies. In a recent study, Nguyen et al (2020) showed that error in Argo's geo-positioned salinity and temperature measurements below 300 m due to limited surfacing opportunities in the Arctic Ocean is smaller than the uncertainty level across most of this ocean, indicating the usefulness of these measurements. At lower depths, the error is often larger, so specific strategies must be adopted.…”
Section: Conclusion On the Use Of Bgc-argo Floats In The Arctic Oceanmentioning
confidence: 99%
“…Moreover, a more comprehensive profiling system (e.g. Nguyen et al ., 2020), comprising Ice‐Thread Profilers (ITPs), moorings and repeated vehicle lines, should be designed, coordinated and evaluated.…”
Section: Discussionmentioning
confidence: 99%